Рlace of tax planning in tax law - Марія Олександрівна Бондаренко (Теорія і практика правознавства, 2017)
The article is dedicated to finding out the place of tax planning  in the tax law. The article is based on the idea of paradoxical tax planning as a legal phenomenon. Great attention is paid to the problem of the lack of strict legitimation of the legal definition, legal nature and its place in the tax law system. It is mentioned that such situation leads to its development both in science and in law. The author notes that it is necessary to determine the type of legal phenomena to understand the legal nature of tax planning to which it belongs. The author analyzes different approaches of the topic. By scientific deepening to the study of the history and legal nature of the term "category". Analyzed not only legal, but also linguistic definition of the term. Based on the analysis, it is concluded that ot is impossibleto to define the term “tax planning”  as a legal category. By taking into account the specificity and peculiarities of tax planning, the author describes it as "legal formation". A particular place of research is given to  the finding out the place of tax planning in the tax law system. According to the analysis of scientist’s point of views about  the concept and components of a legal institute it is concluded that to the tax law is defined as a legal institution, but with some reservations because of its specificity.